Systematics of aquatic beetles (Coleoptera): current state and future directions. (16th October 2017) - SHORT, ANDREW EDWARD Z.
Abstract : Aquatic beetles are a large ecological guild with more than 13, 000 described species occurring worldwide. Our knowledge of the diversity and phylogeny each of the 23 families water beetles is reviewed. Sustained efforts in the past 25 years to illuminate the taxonomy, phylogeny, and ecology of the group have turned it into a model system for many questions in evolutionary biology.